2022
DOI: 10.1101/2022.10.28.514304
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell RNA-seq reveals alterations in peripheralCX3CR1and nonclassical monocytes in familial tauopathy

Abstract: Background: Emerging evidence from mouse models is beginning to elucidate the brain's immune response to tau pathology, but little is known about the nature of this response in humans. In addition, it remains unclear to what extent tau pathology and the local inflammatory response within the brain influence the broader immune system. Methods: To address these questions, we performed single-cell RNA sequencing (scRNA-seq) of peripheral blood mononuclear cells (PBMCs) from carriers of pathogenic variants in MAPT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 112 publications
0
9
0
Order By: Relevance
“…We found that the expansion of ISAG hi T cells relative to PBMCs and all T cells remained significant after addition of these independent controls, although one outlier control sample with very high levels of ISAG hi T cells made the findings somewhat less robust (eFigure 2). We recently reported a reduction in peripheral non-classical monocytes in familial tauopathy 5 . Comparing the familial tauopathy and EOAD datasets, we found that non-classical monocytes are not reduced in EOAD, and ISAG hi T cells are not expanded in familial tauopathy (eFigure 3).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…We found that the expansion of ISAG hi T cells relative to PBMCs and all T cells remained significant after addition of these independent controls, although one outlier control sample with very high levels of ISAG hi T cells made the findings somewhat less robust (eFigure 2). We recently reported a reduction in peripheral non-classical monocytes in familial tauopathy 5 . Comparing the familial tauopathy and EOAD datasets, we found that non-classical monocytes are not reduced in EOAD, and ISAG hi T cells are not expanded in familial tauopathy (eFigure 3).…”
Section: Resultsmentioning
confidence: 94%
“…After obtaining informed consent, PBMCs from study participants (Table 1) at the University of California, San Francisco Memory and Aging Center were analyzed by scRNA-seq essentially as described 5 . Details are described in eMethods.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To increase the sample size of our scRNA-seq dataset, we included seven additional control PBMC samples previously characterized by scRNA-seq. 5 We found that the expansion of ISAG hi T cells relative to PBMCs and all T cells remained significant after addition of these independent controls, despite a single outlier control sample with very high levels of ISAG hi T cells (Supplementary Figure S2). We recently reported a reduction in peripheral non-classical monocytes in familial tauopathy.…”
Section: Analysis Of Isag Hi T-cell Abundance In Additional Samples A...mentioning
confidence: 86%
“…After obtaining informed consent, PBMCs from study participants (Table 1) at the University of California, San Francisco Memory and Aging Center (MAC) were analyzed by scRNA-seq essentially as described. 5 Raw sequencing reads were aligned to GRCh38-2020-A and feature-barcode matrices were generated using Cell Ranger Additional details, including bioinformatic and experimental methods, are described in the Supplementary Methods document and Supplementary Tables S1-S3.…”
Section: Overviewmentioning
confidence: 99%